Analisis Mitigasi Risiko Dan Kesiapsiagaan Bencana Alam Di Kawasan Pariwisata Kuta Mandalika - Rahmad Dwiky Ariyawan; Solikatun Solikatun; Sally Salsabila (Prodi Sosiologi Universitas Mataram, 2025)
Lombok Island has considerable tourism potential, but it also has an equally significant potential for natural disasters. Kuta Village is one of the villages with such potential. Its tourism potential lies in its status as the Mandalika Special Economic Zone (SEZ), while its potential for natural disasters, such as tsunamis and floods, stems from its geographical location bordering the Indonesian Ocean. Therefore, efforts to mitigate risks and prepare for natural disasters are crucial. This study aims to analyze and examine the challenges in the process of risk mitigation and disaster preparedness in the Kuta Mandalika Tourism Area. The theory used in this study is Pierre Bourdieu's Social Practice Theory. This study uses a qualitative approach through the phenomenological study method. Informants were selected using purposive sampling, while data collection was conducted through observation, interviews, and documentation. The results of the study indicate that the implementation of risk mitigation and natural disaster preparedness activities in the Kuta Mandalika tourism area involves various parties and stakeholders. The involvement of these actors and institutions plays a role in the formation of habitus and adds capital to support mitigation and preparedness efforts. The capital available in the arena is transformed into knowledge, networks, and infrastructure facilities to support natural disaster mitigation and preparedness efforts, thereby producing social practices. However, in practice, challenges such as structural barriers, cultural barriers, and participatory barriers act as obstacles in the implementation of risk mitigation and disaster preparedness efforts. These challenges also lead to conflicts arising from the presence of dual arenas, which result in clashes of interests and capital